Web-Based Disruption Service Information System at PT. Telkom Indonesia for Improving Disruption Services - Sayuti, Akhmad; Davizan, Serry; Sari, Indah Rahma; Pramuditho, Anggoro Aryo; Putra, Hasan Pratama; Armiansyah, Rian (Yayasan Insan Mulia Bima, 2025)
PT. Telkom Indonesia is a State-Owned Enterprise (BUMN) engaged in IT, ICT, and telecommunications network services in Indonesia. PT. Telkom Indonesia has services that can be used for individuals and companies, namely Indi home. Indi home is one of the network packages, namely the Indi home Fiber package, which provides internet services, interactive TV, and landline telephones. The obstacle that people sometimes find in reporting complaints about internet disruptions is the very slow handling of internet product repairs. Therefore, a troubleshooting service data system design is needed that can be accessed by customers and the right technicians to support the smooth process, processing of complaint information, and corrective actions. By using the proposed system correctly, it can be easier to monitor the distribution of complaint information so as to speed up the repair process, this can also help speed up the presentation of accurate, timely, and relevant reports so that it can assist management in decision making. This is intended so that technicians do not face significant obstacles in recording information and monitoring the length of time it takes to handle problems in the field. To overcome these problems, a design of an electrical disturbance data service system is needed that can be accessed by the right admin to support the smooth processing of complaint information and corrective actions. So, the conclusion of this research is that this system makes it easier for customers to report WiFi disturbances online without having to come directly to the PT office. Telkom Sekayu. Customers can also see or track where the reported process has progressed.